Incidência de escoliose em alunos do ensino fundamental: revisão bibliográfica - MIRANDA, Merian Souza (2023)
This study has as its theme the postural deviations in elementary school students: Bibliographic Review. The objective of this study was to investigate in the literature the incidence of possible postural deviations, in particular, scoliosis that can be caused by bad posture related to school desks and the use of backpack by elementary school children. Therefore, a literature review of articles related to postural deviations with emphasis on scoliosis was carried out. About 34 articles were found and by exclusion criterion we eliminated 20, about 14 articles were used to investigate the incidence of scoliosis in elementary school students aged between 07 and 12 years. The results showed that the inappropriate use of backpacks and their weight, in addition to the bad posture acquired by students in classrooms, influence the appearance of postural deviations, one of which is scoliosis, in addition to these, another factor that we highlight is incorrect posture. that students assume, which is the result of the discomfort caused by the furniture used in schools. In this sense, we can conclude that scoliosis is present in the school environment, however, these evils can be minimized if compensatory exercises are taught to students to improve posture and prevent possible pain resulting in an improvement in the student's quality of life.